Observation of two-step spin transition in iron(ii) 4-amino-1, 2, 4-triazole based spin crossover nanoparticles. Issue 10 (24th February 2023) - Lalioti, Nikolia; Giannopoulou, Efstathia; Charitos, Alexander; Parthenios, John; Malina, Ondrej; Polaskova, Michaela; Kalarakis, Alexandros; Tangoulis, Vassilis
Abstract : A synthetically controllable two-step spin transition was observed in iron(ii ) spin crossover nanoparticles of the dehydrated one-dimensional coordination polymer [Fe(NH2 trz)3 ]Br2 (NH2 trz = 4-amino-1, 2, 4-triazole) using the reverse micellar method. Abstract : A synthetically controllable two-step spin transition was observed in iron(ii ) spin crossover nanoparticles of the dehydrated one-dimensional coordination polymer [Fe(NH2 trz)3 ]Br2 (NH2 trz = 4-amino-1, 2, 4-triazole) using the reverse micellar method. The change from two-step to one-step hysteretic characteristics succeeded by changing the reaction time.